Para-spermatic cord proximal-type epithelioid sarcoma. Issue 1 (7th January 2021) - Farnan, Jessica; Morrison, Ellen; Hennessey, Derek Barrry
Abstract : Proximal-type epithelioid sarcoma is an ultra-rare, high-grade soft tissue malignancy usually presenting as a deep-seated painless mass in the proximal extremities. Most patients are diagnosed as young adults, between 20 and 40 years of age. Perineal and genital masses do occur but are extremely rare and represent a challenging tumour to diagnose and treat. Early radical excision is recommended due to its aggressive behaviour and poor prognosis. Median overall survival from initial diagnosis is 30 months. We present the case of a 22-year-old man with a left groin proximal-type epithelioid sarcoma who is sadly deceased 12 months after initial presentation despite early surgical excision, completion of both first-line and palliative chemotherapy, and palliative radiotherapy.